Endocrine biomarkers related to sleep-wake cycle and sleep disturbances in patients with bipolar disorder: A systematic review. (1st June 2022) - Gonzalez-Blanco, L.; Moya Lacasa, C.; Jiménez-Fernández, S.; Valtueña, M.; Martinez-Cao, C.; García Fernández, A.; Saiz, P.A.; Garcia-Portilla, M.P.; Bobes, J.; Gutierrez Rojas, L.
Abstract : Introduction: Sleep and circadian disturbances have been widely studied in patients with bipolar disorder (BD) (Duarte Faria et al., 2015; Gonzalez, 2014). However, there is no clear evidence about the role of peripheral biomarkers of circadian cycle in this population. Objectives: This systematic review aims to identify potential endocrine biomarkers of circadian rhythm in blood and study their relationship with sleep problems in BD. Methods: An electronic search of Pubmed and PsycoInfo databases were performed. It includes articles about the topic from 1991 to 2021. The search strategy was: ("Peripheral biomarkers" OR "biological markers" OR biomarker OR cortisol OR melatonin OR orexin OR hypocretin) AND (blood OR serum OR plasma) AND ("sleep-wake" OR "circadian rhythm" OR sleep OR insomnia) AND "bipolar". Results: 92 records were obtained after excluding duplicates. Only five studies met the inclusion criteria (n = 499; BD = 125; unipolar depression = 148; schizophrenia = 80; controls = 146). The endocrine parameters analyzed were: cortisol (3 studies), melatonin (1 study) and orexin-A (1 study). Overall, no significant associations between these biomarkers and sleep disturbances, assessed with subjective (psychometric evaluation) and/or objective (polysomnography) measures, were detected. Conclusions: This systematic review highlights the lack of studies that explores the role of endocrine biomarkers related to circadian function in the pathophysiology of sleep disturbances in BD. Disclosure: No significant relationships.